Implementation and operational research: Integrated pre-antiretroviral therapy screening and treatment for tuberculosis and cryptococcal antigenemia - Pac, Lincoln; Horwitz, Mara Murray; Namutebi, Anne Marion; Auerbach, Brandon J; Semeere, Aggrey; Namulema, Teddy; Schwarz, Miriam; Bbosa, Robert; Muruta, Allan; Meya, David B; Manabe, Yukari C (Journal of acquired immune deficiency syndromes (1999), 2015)
To demonstrate the feasibility of integrated screening for cryptococcal antigenemia and tuberculosis (TB) before antiretroviral therapy (ART) initiation and to assess disease specific and all-cause mortality in the first 6 months of follow-up. We enrolled a cohort of HIV-infected, ART-naive adults with CD4 counts ≤250 cells per microliter in rural Uganda who were followed for 6 months after ART initiation. All subjects underwent screening for TB; those with CD4 ≤100 cells per microliter also had cryptococcal antigen (CrAg) screening. For those who screened positive, standard treatment for TB or preemptive treatment for cryptococcal infection was initiated, followed by ART 2 weeks later. Of 540 participants enrolled, pre-ART screening detected 10.6% (57/540) with prevalent TB and 6.8% (12/177 with CD4 count ≤100 cells/μL) with positive serum CrAg. After ART initiation, 13 (2.4%) patients were diagnosed with TB and 1 patient developed cryptococcal meningitis. Overall 7.2% of participants died (incidence rate 15.6 per 100 person-years at risk). Death rates were significantly higher among subjects with TB and cryptococcal antigenemia compared with subjects without these diagnoses. In multivariate analysis, significant risk factors for mortality were male sex, baseline anemia of hemoglobin ≤10 mg/dL, wasting defined as body mass index ≤15.5 kg/m, and opportunistic infections (TB, positive serum CrAg). Pre-ART screening for opportunistic infections detects many prevalent cases of TB and cryptococcal infection. However, severely immunosuppressed and symptomatic HIV patients continue to experience high mortality after ART initiation.